2008
DOI: 10.1002/adfm.200800487
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembly of Protein Nanoarrays on Block Copolymer Templates

Abstract: There is considerable interest in developing functional protein arrays on the nanoscale for high‐throughput protein‐based array technology, and for the study of biomolecular and cell interactions at the physical scale of the biomolecules. To these ends, self‐assembly based techniques may be desirable for the nanopatterning of proteins on large sample areas without the use of lithography equipment. We present a fast, general approach for patterning proteins (and potentially other biomolecules) on the nanoscale,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
91
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(97 citation statements)
references
References 79 publications
6
91
0
Order By: Relevance
“…As presented in numerous studies, various proteins exhibit biased adsorption to one of the polymeric nanodomains (Figure 7a). [124][125][126][127] For instance, fibrinogen, horseradish peroxidase, or albumin, was found to selectively adsorb onto the PS nanodomains of the diblock copolymer surfaces (Figure 7b). [41] Furthermore, as shown in Figure 7c, protein adsorption is highly favored on the PS region close to the chemical interface defined by the two neighboring PS and PMMA nanodomains.…”
Section: Protein Adsorption On Nanostructured Block Copolymer Surfacesmentioning
confidence: 99%
“…As presented in numerous studies, various proteins exhibit biased adsorption to one of the polymeric nanodomains (Figure 7a). [124][125][126][127] For instance, fibrinogen, horseradish peroxidase, or albumin, was found to selectively adsorb onto the PS nanodomains of the diblock copolymer surfaces (Figure 7b). [41] Furthermore, as shown in Figure 7c, protein adsorption is highly favored on the PS region close to the chemical interface defined by the two neighboring PS and PMMA nanodomains.…”
Section: Protein Adsorption On Nanostructured Block Copolymer Surfacesmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] Previous reports have also explored the effect of a nanopattern on adsorption behavior. For example, the presence of chemical nanostripes with line widths close to that of individual proteins has been shown to induce proteins to preferentially adsorb with an orientation aligned with the nanopattern's anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…PS and PMMA have almost identical surface energies in air, [25][26][27] thus skin layer formation was minimized during PS-b-PMMA block copolymer self-assembly, and topographically flat polymer nanopatterned surfaces could be prepared. 17,24,25 The use of an in situ technique for quantifying protein adsorption ensured that the measurements reflected the native configurations of the proteins adsorbed on the nanopatterned surfaces. Moreover, unlike previous studies that employed an extreme contrast in hydrophobicity to generate a biomolecular response, such as with alkyl/poly(ethylene-oxide) 3,18 or oxide/metal 20 nanopatterns, the PS and PMMA used in this report are both poorly solvated in water and are comparatively similar in hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…Fabricating polymer brushes on a solid substrate is wellknown, and it has been successfully used as an effective way to control surface properties [9]. Taking advantage of the fact that the block copolymer can form regular nanoscale patterns over a macroscopic area via a self-assembly process, spun-cast copolymer films have been utilized in protein patterning and protein adsorption regulating [10][11][12]. Very recently, George et al [8] reported a method for biomaterial surface modification that utilizes the self-assembly of block copolymers of poly(styrene-block-ethylene oxide) (PS-PEO) to generate microphase separated surfaces.…”
Section: Introductionmentioning
confidence: 99%